SPEECH PRODUCTION IN ENGLISH BY STUDENTS WITH HEARING IMPAIRMENT: AN ACOUSTIC PHONETIC APPROACH - Diana Anggraeni; Donal Fernado Lubis; Dini Wulansari (Elite Laboratory English Department Universitas Bangka Belitung, Indonesia, 2023)
Children with special needs have taken wider attentions in research, especially in finding solutions of how to improve their abilities in communication. The purpose of this research is to identify the challenges and barriers in speech production in English by students with hearing impairments in Pangkalpinang City. Investigation and documentation were the main stages in collecting data. The data were studied using a descriptive method with a qualitative approach. Based on the foundation of phonetic theory by Collins and Mess (2019) regarding speech production and the character of children with hearing impairment by Dennis Fry, this research is aimed at analyzing the sounds produced by children with special needs. Experimental observation using the Praat voice analyzer was carried out on students with three types of disabilities: students with vision impairment, hearing impaired, and mental or intellectual disability. The observation results showed that students with hearing impairments (partial and total deafness) were the main concern as their abilities in perceiving and producing speech gave them opportunities to communicate in English despite the barriers, they had to face in pronouncing the words. As conclusion, students with hearing impairment both partial and total deafness produced their speech based on other vocal tracts due to their disability, and certain treatment in speech production should be suggested especially the phonemes involving internal articulators, including alveolar, velar, post-alveolar and nasal sounds. Proximities made in speech showed possibilities to refine their pronunciation.